Mathematical Modeling of Photovoltaic Thermal-Thermoelectric (PVT-TE) Air Collector - Nurul Syakirah Nazri; Ahmad Fudholi; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Photovoltaic (PV) cell from solar energy is one of the most widely adopted renewable energy source and commercially available system that can be used in various applications. More appealing application of PV arrays used in thermoelectric (TE) device was it can convert solar thermal energy from temperature difference into electric energy to act as power generators. In this study, a theoretical model is developed by using conducting steady state energy analysis of a PVT-TE air collector. The matrix inversion method is used to obtain energy balance equation. The effect of various parameters also investigated. The mass flow rate of range 0.01 kg/s to 0.05 kg/s and solar intensity of 400 W/m2, 600 W/m2 and 800 W/m2 was used to obtain outlet temperature, To in the range about 28.9oC to 43.7oC and PV temperature, Tp about 35.3oC to 60oC.